Restraining Yourself : Fiscal Rules and Stabilization - Eichengreen, Barry (IMF Working Papers; Working Paper ;, 1994)
State budgets in the United States played a significant macroeconomic role in the 1970s and 1980s, and the level of cyclical responsiveness was affected by the severity of statutory and constitutional fiscal restraints. Moving from no fiscal restraints to the most stringent restraints lowered the fiscal offset to income fluctuations by around 40 percent. Simulations indicate that a reduction in aggregate fiscal stabilizers of this size could lead to a significant increase in the variance of aggregate output.